ANALYSIS OF VOCATIONAL TEACHER TRAINING NEEDS FOR PKK SUBJECTS (CREATIVE PROJECTS AND ENTREPRENEURSHIP) - Astuti, Widya Puji; Hernawan, Asep Herry (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Several previous studies have revealed that training provides positive and significant benefits to employees. Vocational school teachers are seen as needing to improve their competence in order to meet the demands of their work. This research aims to conduct an analysis of the training needs for vocational school teachers who teach PKK subjects within the framework of the Merdeka Curriculum. Survey methods and quantitative approaches are the methods and approaches applied in this research. The population in this study was 22 teachers who taught PKK (Creative Projects and Entrepreneurship) subjects at SMKN 1 Pacet Cianjur. The sampling technique used in this research was saturated sampling. Data collection in this research used a questionnaire prepared on a Likert scale. The data in this study were analyzed using descriptive statistics. The results obtained in this study indicate that teachers at SMKN 1 Pacet Cianjur who teach PKK (Creative Projects and Entrepreneurship) subjects need training to improve and develop their competencies. The majority of teachers consider that they need advanced training about PKK subjects. The advanced level training teachers require is focused on training regarding learning materials and implementation of learning. The implications of the research show that educational institutions need to prioritize developing the competencies of their teachers and provide training that is able to meet the needs identified in this research.